ANALYSIS OF IMPORTANCE AND PERFORMANCE LEVELS AND CONSUMER SATISFACTION TOWARD CASSAVA CHIPS PRODUCTS AT ROBBANI SNACK MSME - Nurainy, Fibra; Setiawan, Teguh; Satyajaya, Wisnu; Amelia, Della (Jurusan Teknologi Hasil Pertanian, 2025)
Robbani Snack was a micro, small, and medium enterprise (MSME) located in Gading Rejo District, Pringsewu Regency, Lampung. It was established in 2010 and operated in the snack food sector. At the time, Robbani Snack’s cassava chips experienced a decline in sales (slow-moving), and in some cases, they were sold close to their expiration dates. This condition indicated the need for an analysis of the importance and performance level of product attributes, as well as consumer satisfaction, in order to determine improvement priorities and enhance competitiveness. The study aimed to identify consumer characteristics, analyze the importance and performance levels, and assess consumer satisfaction with Robbani Snack's cassava chips product based on the 4P marketing mix (product, price, promotion, and place). This research employed descriptive analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI) to achieve its objectives. The results based on the IPA showed that the attributes in quadrant I (top priority) included uniformity of shape, packaging design, and ease of product availability. Attributes in quadrant II (maintain performance) included taste, crispiness, halal label, expiration date, price, and the location and convenience of purchase. Attributes in quadrant III (low priority) included flavor variants, color, packaging size, social media advertising, and specific discount offers, while quadrant IV (excessive) included thickness and discount offers during certain events. The Customer Satisfaction Index (CSI) calculation showed a consumer satisfaction level of 77.02%, indicating that the product had met consumer expectations. Keywords: Cassava chips, IPA, CSI